The receptor-like kinase SOBIR1 interacts with Brassica napus LepR3 and is required for Leptosphaeria maculans AvrLm1-triggered immunity - Ma, Lisong; Borhan, M. Hossein (Frontiers in Plant Science, 2015)
Abstract The fungus Leptosphaeria maculans (L. maculans) is the causal agent of blackleg disease of canola/oilseed rape (Brassica napus) worldwide. We previously reported cloning of the B. napus blackleg resistance gene, LepR3, which encodes a receptor-like protein. LepR3 triggers localised cell death upon recognition of its cognate Avr protein, AvrLm1. Here, we exploited the Nicotiana benthamiana model plant to investigate the recognition mechanism of AvrLm1 by LepR3. Co-expression of the LepR3/AvrLm1 gene pair in N. benthamiana resulted in development of a hypersensitive response (HR). However, a truncated AvrLm1 lacking its indigenous signal peptide was compromised in its ability to induce LepR3-mediated HR, indicating that AvrLm1 is perceived by LepR3 extracellularly. Structure-function analysis of the AvrLm1 protein revealed that the C-terminal region of AvrLm1 was required for LepR3-mediated HR in N. benthamiana and for resistance to L. maculans in B. napus. LepR3 was shown to be physically interacting with the B. napus receptor like kinase, SOBIR1 (BnSOBIR1). Silencing of NbSOBIR1 or NbSERK3 (BAK1) compromised LepR3-AvrLm1-dependent HR in N. benthamiana, suggesting that LepR3-mediated resistance to L. maculans in B. napus requires SOBIR1 and BAK1/SERK3. Using this model system, we determined that BnSOBIR1 and SERK3/BAK1 are essential partners in the LepR3 signalling complex and were able to define the AvrLm1 effector domain.